Development of a novel fusion system for soluble protein overexpression and purification in Escherichia coli - Costa, Sofia Judite (2010)
Recombinant protein production is a useful technology for therapeutic and diagnostic applications. The bacterium Escherichia coli is widely used for the bioproduction of proteins, but still presents some drawbacks. Recombinant proteins with biomedical interest have proved difficult to express properly in this host system, resulting in insoluble protein aggregates. Fusion protein technology has been applied to overcome these drawbacks and to optimize protein expression in E. coli. This research aims at the evaluation of a novel fusion system (Fh8 and H tags) effects on protein production. Target proteins used in this work present biomedical interest and results obtained here showed that these novel fusion tags increased protein production yields. This novel fusion system is a promising tool for the production of recombinant proteins with biomedical interest.